The ESTELA project and its most recent results (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
Some of the most significant results of the work developed under the ESTELA project are presented, namely the last results of the archaeological research at Abóboda necropolis, the excavations in Portela da Arca habitat (Almodôvar), and the geophysical survey in Monte/Vale dos Vermelhos and Corte Pinheiro 1 (Loulé). Attention is paid to some issues related to certain problematic monuments, giving a contribution to improve the corpus of pre-Roman southwestern Iberia scripts. Finally, we pay attention to some of the most recent epigraphic finds: a recently published graffito from Porto do Sabugueiro (Salvaterra de Magos), and an unpublished stella from Monte Gonçalo Eanes (Almodôvar).